Self-Visualization In Cyber Space Between Front Stage And Back Stage (Case Study Of Instagram Account Owner @Kulinercirebon) - Valda Fadhila; Auliya Utami; Khaerudin Imawan; Dedet Erawati (International Journal Labs, 2024)
Nowadays, people often use social media, especially Instagram, to create an interesting impression for the audience. However, the content created often differs from reality. This research aims to find out how to use social media @kulinercirebon to manage impressions through Front Stage and Back Stage analysis on Instagram social media. This research uses qualitative methods with analysis that refers to Erving Goffman's Dramaturgical theory. The research results show that from the Front Stage side, the owner of the Instagram account @kulinercirebon tries to give an interesting impression of the culinary delights in Cirebon. The @kulinercirebon account displays various interesting and informative photos and videos, depicting typical Cirebon food in an appetizing way, while from the back stage, the owner of the @kulinercirebon account often responds to various questions that arise via direct messages on Instagram. Apart from that, the owner of the @kulinercirebon account also uses his social media account as a paid promotional medium for business people who want to promote the place they own. The conclusion of this research shows that the owner of the Instagram account @kulinercirebon manages his account according to his main goal, namely introducing culinary places in the Cirebon area.